A formula for the number of labelled trees - Vites Longani (2018)
Let L (n, r) be the number of labelled trees with n points and r end-points. In this paper it is shown that the number L (n, r) can be obtained from the formula L (n, r) = fenced(frac(n, n - r)) underover(∑, i = 0, n - r - 1) (- 1)i fenced(frac(n - r, i)) (n - r - i)n - 2 . © 2008 Elsevier Ltd. All rights reserved.